Simple adaptive control to attenuate bridge's seismic responses considering parametric variations. Issue 1 (January 2020) - Soares, Rachel W; Barroso, Luciana R; Al-Fahdawi, Omar AS
Parametric variations occur throughout a bridge's service life as a result of temperature variations, cracking, localized damage, and fatigue. Existing bridge's parameters are difficult to estimate precisely and implemented control schemes may perform unsatisfactorily depending on how sensitive they are to parametric change. In this study, an adaptive control approach is developed utilizing the simple adaptive control algorithm and designed aiming to mitigate seismic responses of bridges considering realistic implementation. Adaptive control is a viable alternative to control bridge structures as it is able to calculate control gains that vary over time based on sensed responses, sustaining performance in face of parametric variations. The proposed approach allows the choice of a model reference of significantly low order and it does not require full-state feedback or the use of observers. The effectiveness and robustness of the control approach are investigated when controlling a seismically excited two-span highway bridge considering systematic parametric variations. Evaluation of relevant performance criteria indicates that the adaptive scheme is effective in reducing seismic responses and sustains well the overall performance when systematic parametric variations are introduced. The proposed approach requires a small and reasonable number of sensors to present effectiveness and performs satisfactorily even when in the presence of measurement noise.